THEORETICAL STUDY ON INTERACTIONS BETWEEN IONIC LIQUID AND CHITIN/CHITOSAN/ CELLULOSE - Lü, Renqing; Lin, Jin; Zhao, Xin (Journal of the Chilean Chemical Society, 2018)
In order to deepen understanding the interactions between ionic liquid and chitin/chitosan/ cellulose at the molecular level, we have performed a study on the electronic structures, topological properties, nonconvalent interactions between 1-ethyl-3-methyl imidazolium chloride and chitin/chitosan/cellulose by using density functional theory. The results indicate that interactions between chitin/chitosan/cellulose and 1-ethyl-3-methyl imidazolium chloride are stronger that the intra-interaction of chitin/chitosan/cellulose, implying that chitin/ chitosan/ cellulose can dissolve in 1-ethyl-3-methyl imidazolium chloride.